THE RATIONALE BEHIND CRYPTOCURRENCY TAXATION AND GLOBAL TRENDS - Zdolšek, Daniel; Taškar Beloglavec, Sabina (Ekonomski pogledi, 2025)
This conference paper examines the rationale behind taxing cryptocurrency operations and the current regulatory frameworks governing them. As the significance and value of crypto-assets rose and became a crucial potential investment, embraced by numerous investors, the importance of their typologization, classification, and definition has also increased. Crypto-assets were initially issued as currency, a term often used to describe this concept, and, therefore, serve as a medium of exchange or a digital payment method. However, with time, they have increasingly evolved into speculative investment assets. Bitcoin, first introduced in 2008 as a response to financial crises, is a classic example of speculative investment. Given the potential returns on the sale of cryptocurrencies and the lack of regulation in this area, particularly in comparison with traditional financial instruments such as shares, the taxation of cryptocurrencies is a key issue for existing and potential investors, regulators, and governments worldwide. The transformation of cryptocurrencies into crypto-assets raises a few critical questions: (1) why should crypto-assets be taxed, and (2) which are already established global platforms for crypto taxation. International recommendations concerning what aspects of crypto activity should be taxed—and how—are crucial for enhancing transparency in crypto markets and curbing potential misuse. Moreover, the lack of clarity in terminology and substance continues to create confusion, which this article aims to address.